Effect of Dormancy Treatments on Seed Quality and Storability of Stylosanthes hamata - SR KAVITA; VINOD KUMAR; K SRIDHAR; B S VYAKARNAHAL; B C CHANAPPAGOUDAR (Seed Research, 2026)
Stylosanthes hamata cu, verano, which is an important forage legume, offers fodder for livestock, but its establishment in field is very poor because of hard seeded nature. Hence, it is important to reduce the hard seed content in a lot, for successful germination and uniform seedling emergence. In the present study, the germination and other parameters of Stylosanthes hamata seeds were tested under three types of dormancy breaking treatments. For physical treatment, hot water, hot air oven and smoke treatment were used. Mechanical treatment was performed by hand scarification using sandpaper and chemical treatment by sulphuric acid, sodium hydroxide, polyethylene glycol-6000 and ethrel solutions. The results revealed that, fresh seeds (control) recorded zero per cent germination initially, while mechanical scarification with sand paper recorded the highest germination (40.0%) and seedling vigour index (335) initially. Similarly, at the end of eleven months of storage, the highest percentage of germination (73.5%) and vigour index (656) were obtained in mechanically scarified seeds (T₁) followed by acid scarification with conc. H₂SO₄ for 2 min. (43.8% and 376, respectively) along with the reduction of hard seededness. Maximum dead seeds (23.0%) were recorded in seeds soaked in hot water.